K-Pop sebagai Budaya Populer dalam Kegiatan Ekstrakurikuler Modern Dance di SMP Labschool UNESA 2 Surabaya: SMP Labschool UNESA 2 Surabaya - Arianti Cahyadiningrum; Autar Abdillah (Universitas Negeri Surabaya, 2025)
The rise of South Korean popular culture (K-Pop) has influenced various aspects of life, including school extracurricular activities designed to foster students' interests and talents. This study analyzes the use of K-Pop as a reference point for the Modern Dance extracurricular program at SMP Labschool UNESA 2 Surabaya, examining its presence in training materials, the role of K-Pop idols as a source of motivation, and its impact on student competence. A qualitative, descriptive research approach was employed, grounded in theories of popular culture, hybridity, cultural proximity, and achievement motivation. Data sources included the extracurricular instructor, the student affairs coordinator, student affairs staff, and the students themselves. Data were collected through observation, interviews, and documentation, utilizing corresponding guidelines and records. Data validity was verified through source and technique triangulation, while analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The findings indicate that K-Pop serves as a reference for modern dance instruction through the use of songs and adapted choreography thereby enhancing students' motivation, discipline, teamwork, self-confidence, and non-academic achievements. The study concludes that K-Pop culture can be positively utilized as a learning medium within modern dance extracurricular activities. Schools are encouraged to develop extracurricular activities that adapt to popular culture while upholding educational values.